Characteristics of Spanish exojournalists: new professional profile in the era of artificial intelligence - Ufarte Ruiz, María José (2024)
profile of the journalist, forcing them to master the tools used by this technology. This research approaches the figure of the exojournalist, an emerging professional profile that connects the possibilities of artificial intelligence with the specific needs of news production routines. The process to achieve this goal is articulated around a triangular methodology that combines qualitative and quantitative techniques. Semi-structured interviews have been conducted with professors from Spanish universities who are experts in the field and with journalists with a recognized career in the communication sector. The interviews have revolved around three thematic axes: 1) skills and competences; 2) new profiles; 3) transformation of newsrooms. Secondly, participant observation has been carried out in the Newtral newsroom, which is working on the development of a verification system based on artificial intelligence. The purpose of this technique is to know the specific skills and competences that workers have in the development of automated content. Finally, a questionnaire has been distributed among the members of this medium, with the purpose of knowing the routines and tasks they perform and analyzing the competences and skills they possess. The results reflect that there is not a single profile for artificial intelligence, but that Spanish exojournalists know computational language and are equipped with heterogeneous technical and linguistic skills that allow them to document, verify and generate content from a transmedia logic and from different approaches.